RIM-Binding Proteins Are Required for Normal Sound-Encoding at Afferent Inner Hair Cell Synapses - Krinner, Stefanie; Predoehl, Friederike; Burfeind, Dinah; Vogl, Christian; Moser, Tobias (Frontiers in Molecular Neuroscience, 2021)
The afferent synapses between inner hair cells (IHC) and spiral ganglion neurons are specialized to faithfully encode sound with sub-millisecond precision over prolonged periods of time. Here, we studied the role of RIM-binding proteins (RIM-BP) 1 and 2 – multidomain proteins of the active zone known to directly interact with Rab3 interacting molecules (RIMs), Bassoon and CaV1.3 – in IHC presynaptic function and hearing. Recordings of auditory brainstem responses and otoacoustic emissions revealed that genetic disruption of RIM-BPs 1 and 2 in mice (RIM-BP1/2-/-) causes a synaptopathic hearing impairment exceeding that found in mice lacking RIM-BP2 (RIM-BP2-/-). Patch-clamp recordings from RIM-BP1/2-/- IHCs indicated a subtle impairment of exocytosis from the readily releasable pool of synaptic vesicles that had not been observed in RIM-BP2-/- IHCs. In contrast, the reduction of Ca2+-influx and sustained exocytosis was better preserved in RIM-BP1/2-/- IHCs. We conclude that both RIM-BPs are required for normal sound encoding at the inner hair cell synapse, whereby RIM-BP2 seems to take the leading role.